"The complaining women": health professionals' perceptions on patients with fibromyalgia in Spain. Issue 14 (3rd July 2018) - Briones-Vozmediano, Erica; Öhman, Ann; Goicolea, Isabel; Vives-Cases, Carmen
Abstract: Purpose : The aim of this study is twofold: (1) to explore health service providers' perceptions regarding fibromyalgia patients in Spain and (2) to analyze possible consequences of these perceptions in terms of how health service providers construct the disease and treat their patients. Design: Qualitative study. Subjects/Patients: Twelve health service providers (eight men, four women) involved in the care of fibromyalgia patients. Providers were from different disciplines and included general practitioners, rheumatologists, occupational doctors, psychologists, psychiatrists, physiotherapists and behavioral specialists from Spain. Method: We performed individual semistructured interviews, which were recorded and transcribed to conduct a qualitative content analysis supported by Atlas.ti-7. Results: We identified three categories from the interviews: (1) the fibromyalgia patient prototype: the complaining woman, (2) fibromyalgia is considered a women's health issue, but male patients are a privileged minority, and (3) health professionals' attitudes toward fibromyalgia patients: are they really suffering or pretending? Conclusion: The uncertainty surrounding fibromyalgia together with the fact that those affected are primarily women, seem to influence professional practice in terms of lack of recognition of Fibromyalgia as a severe disease. Increased training of all health professionals is essential to improving the support and attention given to patients suffering from fibromyalgia. Implications for rehabilitation:   Fibromyalgia    In order to improve fibromyalgia patients´ attention, health providers should learn how to assist patients without prejudices.    Training programs for health providers should include sensitization about the severity of fibromyalgia.    Health providers should be aware of the existence of stereotypes about women suffering from fibromyalgia.    Fibromyalgia protocols should give skills to health providers to avoid offering a gender-biased attention to patients.